Intra-abdominal pressure correlates with abdominal wall tension during clinical evaluation tests. (August 2021) - Novak, Jakub; Jacisko, Jakub; Busch, Andrew; Cerny, Pavel; Stribrny, Martin; Kovari, Martina; Podskalska, Patricie; Kolar, Pavel; Kobesova, Alena
Abstract: Background: The abdominal muscles play an important respiratory and stabilization role, and in coordination with other muscles regulate the intra-abdominal pressure stabilizing the spine. The evaluation of postural trunk muscle function is critical in clinical assessments of patients with musculoskeletal pain and dysfunction. This study evaluates the relationship between intra-abdominal pressure measured as anorectal pressure with objective abdominal wall tension recorded by mechanical-pneumatic-electronic sensors. Methods: In a cross-sectional observational study, thirty-one asymptomatic participants (mean age = 26.77 ± 3.01 years) underwent testing to measure intra-abdominal pressure via anorectal manometry, along with abdominal wall tension measured by sensors attached to a trunk brace (DNS Brace). They were evaluated in five different standing postural-respiratory situations: resting breathing, Valsalva maneuver, Müller's maneuver, instructed breathing, loaded breathing when holding a dumbbell. Findings: Strong correlations were demonstrated between anorectal manometry and DNS Brace measurements in all scenarios; and DNS Brace values significantly predicted intra-abdominal pressure values for all scenarios: resting breathing ( r = 0.735, r 2 = 0.541, p < 0.001), Valsalva maneuver ( r = 0.836, r 2 = 0.699, p < 0.001), Müller's maneuver ( r = 0.651, r 2 = 0.423, p < 0.001), instructed breathing ( r = 0.708, r 2 = 0.501, p < 0.001), and loaded breathing ( r = 0.921, r 2 = 0.848, p < 0.001). Interpretation: Intra-abdominal pressure is strongly correlated with, and predicted by abdominal wall tension monitored above the inguinal ligament and in the area of superior trigonum lumbale. This study demonstrates that intra-abdominal pressure can be evaluated indirectly by monitoring the abdominal wall tension. Highlights: Pressure sensors measure abdominal wall tension Pressure sensors indirectly evaluate intra-abdominal pressure. Increases in abdominal wall tension correlate with intra-abdominal pressure changes. Abdominal wall tension increases in five postural-respiratory scenarios. Intra-abdominal pressure increases in five postural-respiratory scenarios.